The Effect of Liquid Extract Organic Fertilizer of Centrosema (Centrosema pubescens) Leaf Sheats on The Growth and Biomass Production of Elephant Grass (Pennisetum purpureum) - Mukhtar, Muhammad; Astawa, I Komang (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
This research was aimed to determine the effect of Â liquid extract organic fertilizer ofÂ centrosema (Centrosema pubescens) leaf sheets on the growth and biomass production of Â elephantgrass (Pennisetum purpureum). This research used complete random sampling method with fivetreatments and three replications by using polybag as a planting media. The treatments conductedwere P0 (0 ml liquid fertilizer/plant), P1 (10 ml liquid fertilizer/plant), P2 (20 ml liquidfertilizer/plant), P3 (30 ml liquid fertilizer/plant), P4 (40 ml liquid fertilizer/plant). The parametersobserved were the growth of plant height, tiller number, fresh biomass production and leaf bladepercentage of elephant grass. The results showed that the treatments were significantly affected onplant height, tiller number, fresh biomass production and leaf blade percentage of elephant grass.Each treatment obtained best results such as in plant height was reached at P3 (135 cm), tillernumber and fresh biomass productions were reached at P4 (8,33 plants and 291,67 gr) and leafblade percentage was reached at P1 (55,31%).Key Words: Centrosema Leaf Sheath, Growth, Biomass Production, Elephant Grass